The construction of "Group". A dialogue: Cherán - Lopez Espinosa, Liliana (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
"Thinking on your own" was a statement that Louis Althusser alluded to imply the historical idea of ​​Karl Marx, in this sense the statement beyond a semantic range, it is thus understood, which, as an extension of speech, ((( "All discussion is not only for words, but also for them": Althusser). Alberto Híjar in the same way, he refers, in turn, his importance, and makes his work an effort to give each theoretical demarcation an ideal discernment of terms, because as such, they are also concepts. And in another sense: politics. Thinking about a project on its own account implies thinking in the case of Cherán and the EZLN, it seems to me that the case of Cherán scale at organizational and community levels, since the budgets established by the organizations that make it up are met. It is, as a result of promoting projects that point to truly autonomic utopia, because in the importance of processing the presence of a historical sense, from the present, it configures a necessary characteristic of valuation in the theory to promote changes in social praxis.